(untitled) (Modern education and development, 2025)
Artificial intelligence (AI) has emerged as a transformative force in modern military operations, enhancing decision-making processes, operational efficiency, and the effectiveness of defense strategies. The application of AI in the military encompasses a wide range of areas, including autonomous weapons systems, cyber defense, intelligence gathering, logistics optimization, and battlefield management. This paper explores the various ways AI is integrated into military operations, focusing on the strategic advantages, challenges, and ethical considerations associated with its use. AI technologies, such as machine learning, computer vision, and natural language processing, are revolutionizing how military forces analyze data, conduct surveillance, and engage in combat. However, the integration of AI into military systems raises significant concerns related to security, accountability, and the potential for escalation of conflicts. This paper examines these issues and proposes recommendations for the responsible and ethical application of AI in the military, ensuring that it enhances national security while mitigating risks.